2003
DOI: 10.1104/pp.102.010397
|View full text |Cite
|
Sign up to set email alerts
|

Ethylmethanesulfonate Saturation Mutagenesis in Arabidopsis to Determine Frequency of Herbicide Resistance

Abstract: Plant resistance to glyphosate has been reported far less frequently than resistance to sulfonylurea and imidazolinone herbicides. However, these studies tend to be anecdotal, without side by side comparisons for a single species or natural isolate. In this study, we tested the frequencies of resistance of three herbicides in a controlled ethylmethanesulfonate (EMS) saturation mutagenesis experiment, allowing a direct comparison of the frequencies at which resistant mutant plants arise. The 100% growth inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 29 publications
1
109
2
2
Order By: Relevance
“…Additionally, a single cycle of selection with diclofop-methyl increased populationlevel resistance to a range of other herbicides (Figure 2), demonstrating the potential for rapid selection of diverse cross-resistance patterns. These observed phenotypic frequencies of resistance were orders of magnitude greater than rates of spontaneous target-site mutations, which give rise to target-site ALS resistance in Arabidopsis thaliana (Haughn and Somerville, 1987;Jander et al, 2003) and Nicotiana tabacum (Harms and DiMaio, 1991). These frequencies were also much greater than the initial frequency of target-site based resistance to ALS herbicides in three previously untreated L. rigidum populations (Preston and Powles, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, a single cycle of selection with diclofop-methyl increased populationlevel resistance to a range of other herbicides (Figure 2), demonstrating the potential for rapid selection of diverse cross-resistance patterns. These observed phenotypic frequencies of resistance were orders of magnitude greater than rates of spontaneous target-site mutations, which give rise to target-site ALS resistance in Arabidopsis thaliana (Haughn and Somerville, 1987;Jander et al, 2003) and Nicotiana tabacum (Harms and DiMaio, 1991). These frequencies were also much greater than the initial frequency of target-site based resistance to ALS herbicides in three previously untreated L. rigidum populations (Preston and Powles, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…This cross design was replicated six times, giving six triple-heterozygous resistant-susceptible (R/S) plants (called the G2 family), each used to originate a segregating family (G3). The EMS origin of the csr1-1, ixr1-2, and axr1-3 lines means that they may carry several mutations other than the ones conferring resistance ( Jander et al 2003). By our crossing protocol, any EMS mutations other than the ones conferring resistance (except those closely linked to the resistance mutations) would contribute equally to the average fitness of each of the 27 genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…To limit maternal effects among crosses, all F1 plants were grown at the same time in a greenhouse, under natural light supplemented by artificial light to provide a 16-h photoperiod and temperature maintained between 20 and 25 1C. The EMS origin of the axr1-3 line means that it may carry several mutations other than the ones conferring resistance (Jander et al, 2003). In a previous study, EMS mutations other than the one conferring axr1-3 resistance were found not to induce a significant reduction of plant fitness .…”
Section: Plant Materialsmentioning
confidence: 99%